Щит на вратах - Посняков Андрей Анатольевич (Историческая авантюра, 2007)
Экземпляры: АБ (20171013) / Инвентарный номер: 47459 / Цена: 150.00 / Сис.шифр: Р2 / Авт.знак: П 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6